Experimental study on the isothermal low-temperature oxidation behavior and kinetics of light oil using TG-FTIR - Xu, Chunyun; Pu, Wanfen; Zhao, Shuai; Zhang, Fang; Wang, Hao; Wang, Shengjia (Journal of thermal analysis and calorimetry, 2025)
A great quality of light oil often experienced various degrees of isothermal low-temperature oxidation (LTO) reactions in the processes of high-pressure air injection, storage, and transportation, which received insufficient attention. Therefore, a comprehensive investigation into the isothermal LTO behavior of light oil is of vital significance. In this study, thermogravimetry coupled with Fourier transform infrared spectroscopy was used to study the LTO behavior of light oil at seven different temperatures (50, 100, 150, 200, 250, 300, and 350 °C) under isothermal conditions. Subsequently, the principal component analysis (PCA) was employed to facilitate a comprehensive examination of the LTO reaction process. Furthermore, the isothermal oxidation kinetics of light oil was investigated through the n -order model. The isothermal TG and PCA results indicated that the LTO of light oil could be divided into three stages. Subsequently, the FTIR results revealed the main reaction pathways of three stages. The isothermal kinetic results indicated that a rapid increase of reaction rate was observed from 200 to 250 °C, suggesting a heightened reactivity of light oil due to its increased polar molecular structure during LTO.